Editorial: anxiety and depression in inflammatory bowel disease. Issue 6 (21st August 2018) - Mikocka‐Walus, A.; Knowles, S. R.
Abstract : This article is linked to Stapersma et al papers. To view these articles visithttps://doi.org/10.1111/apt.14865 andhttps://doi.org/10.1111/apt.14928 .